2010
DOI: 10.1111/j.1365-2966.2010.17080.x
|View full text |Cite
|
Sign up to set email alerts
|

Early-type galaxies at large galactocentric radii - II. Metallicity gradients and the [Z/H]-mass, [α/Fe]-mass relations

Abstract: We present the results of a study of stellar population properties at large galactocentric radii of 14 low‐mass early‐type galaxies in the Fornax and Virgo clusters. We derive radial profiles of age, total metallicity [Z/H] and [α/Fe] abundance ratios out to ∼1–3 effective radii by using nearly all of the Lick/IDS absorption‐line indices in comparison to recent single stellar population models. We extend our study to higher galaxy mass via a novel literature compilation of 37 early‐type galaxies, which provide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

51
175
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(229 citation statements)
references
References 95 publications
51
175
0
Order By: Relevance
“…When AGN feedback is included, a number of galaxies move towards the observed relations for earlytype galaxies (Kuntschner et al 2010;Spolaor et al 2010;Johansson et al 2012, note that all simulated galaxies are displayed). For log σ 2.1, the relation is reversed when AGN is included, more in keeping with observations.…”
Section: [α/Fe] -Velocity Dispersion Relationmentioning
confidence: 90%
See 1 more Smart Citation
“…When AGN feedback is included, a number of galaxies move towards the observed relations for earlytype galaxies (Kuntschner et al 2010;Spolaor et al 2010;Johansson et al 2012, note that all simulated galaxies are displayed). For log σ 2.1, the relation is reversed when AGN is included, more in keeping with observations.…”
Section: [α/Fe] -Velocity Dispersion Relationmentioning
confidence: 90%
“…Observational data show a tight relation between [α/Fe] and galaxy mass for both central values (Thomas et al 2003;Johansson et al 2012) and values within Re (Kuntschner et al 2010;Spolaor et al 2010), although the slope and absolute values depend on the analysis of the observed absorption lines. The aperture effect should be negligible as the observed radial gradient of [α/Fe] is very small.…”
Section: [α/Fe] -Velocity Dispersion Relationmentioning
confidence: 97%
“…Since then, a large amount of work has been done measuring alphaelement abundances to study this trend in all sort of environments (e.g. Worthey et al 1992;Trager et al 2000;Kuntschner 2000;Bernardi et al 2006;Sánchez-Blázquez et al 2006;Spolaor et al 2010; Thomas et al 2010).…”
mentioning
confidence: 99%
“…This process explains the trend in the [α/Fe]-σ relation at σ 100 km s −1 . For less massive galaxies with σ 100 km s −1 , which are not affected by AGN feedback, [α/Fe] is nearly constant; this behaviour might be inconsistent with the observations which suggest that the [α/Fe]-σ trend exists at least for σ 10 1.7 km s −1 (Spolaor et al 2010;Johansson et al 2012).…”
Section: S U M M a Ry A N D Discussionmentioning
confidence: 77%
“…Below σ ∼ 100 km s −1 , [α/Fe] becomes nearly constant, while the observational trend continues at least down to σ ∼ 10 1.7 km s −1 (e.g. Spolaor et al 2010;Johansson et al 2012). The star-forming galaxies, in the reference simulation, exist below σ ∼ 10 2.1 km s −1 and have slightly lower [α/Fe] than the passive galaxies.…”
Section: The α-To-fe Ratios Of Simulated Galaxiesmentioning
confidence: 95%